Inhibition of Pasteurella multocida Adhesion to Rabbit Respiratory Epithelium Using Lectins. (24th February 2015) - Carrillo, Magda Patricia; Martinez, Nhora María; Patiño, María del Pilar; Iregui, Carlos Arturo
Abstract : This study aimed to evaluate the ability of a panel of lectins to inhibit the ability of Pasteurella multocida to adhere to and affect the rabbit respiratory epithelium. Nasal septa from rabbit fetuses were cultured with various lectins before the addition of P. multocida . The percentage of bacteria adhering to the epithelium was evaluated semiquantitatively by indirect immunoperoxidase (IIP) staining. The goblet cells (GCs) were counted in semithin sections stained with toluidine blue and served as the main morphological criterion to evaluate the inhibitory effect of the lectins. The lectins PNA, WGA, RCA120, and DBA significantly inhibited the adhesion of P. multocida to the ciliated epitheliumP < 0.05 and prevented the pathogen-induced increase in the number of GCsP < 0.05 compared with those of positive control tissues. In addition, VVA, SJA, UEA I, DSL, SBA, and ECL significantly inhibited the increase in GCs compared with that of the control tissues. The results suggest that less aggressive therapeutic strategies, such as treatment with lectins, may represent alternative approaches to control bacterial respiratory infections.